Topology in the fruit plantation - Riczu, Péter; Tamás, János (Acta Agraria Debreceniensis, 2012)
The localization of fruit trees, the topology of the branch structure and the spatial structure of the canopy are important to plan sitespecific agro-ecological and production technology projects in an orchard. The currently used instruments and technologies – in the precision agriculture – give opportunities to obtain these informations. The examinations were carried out in the Study and Regional Research Farm of the University of Debrecen near Pallag with the use of a GreenSeeker 505 Hand Held™ Optical Sensor Unit, and its interface the Trimble AgGPS FmX Integrated Display board computer. The collected spectral data were completed with the 3D point cloud by Leica ScanStation C10 laser scanner. The laser impulse data and the vegetation index values were integrated in a unified 3D system. The integration of the two special data collection system provides new opportunities in the development of precision production technology system. The results could be directly used in phytotechnology, water management, plant protection and harvesting in orchards. Our elaborated method can supply digital high spatial accuracy guidance data for development of the automated machines, which could provide some new developmental way in the immediate future.